THE ROLE OF LEXICOLOGY IN THE STUDY OF THE ENGLISH LANGUAGE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Lexicology, the branch of linguistics that deals with the study of words, their meanings, structures, and functions, plays a crucial role in understanding the English language. This article explores the significance of lexicology in English language studies, focusing on word formation, semantic changes, and the relationship between lexical and syntactic structures. It examines the impact of historical and social changes on the English lexicon and the evolution of word usage across different registers and dialects.